2020
DOI: 10.2486/indhealth.2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

Associations of job-related hazards and personal factors with occupational injuries at continuous miner worksites in underground coal mines: a matched case-control study in Indian coal mine workers

Abstract: A wide range of job-related hazards and personal factors may be associated with injury occurrences at continuous miner worksites but their role has been little documented. To address this issue, a case-control study in India was conducted to compare 135 workers with an injury during the previous 2-year period and 270 controls without injury during the previous 5-year period (two controls for each injured worker, matched on age and occupation). Data were collected through face-to-face interviews using standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Widanarko et al [ 36 ] confirmed that occupational diseases with lower-back symptoms caused miners’ absenteeism to grow and reduce the productivity of individuals. Life-safety risks (i.e., occupational risks) in the workplace may impair several aspects, such as individual health or job performance [ 37 ]. According to the COR theory, when an individual’s resources are lost and fail to produce the expected return after a large amount of resource investment, the anxiety and job performance generated by work stress increase.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Widanarko et al [ 36 ] confirmed that occupational diseases with lower-back symptoms caused miners’ absenteeism to grow and reduce the productivity of individuals. Life-safety risks (i.e., occupational risks) in the workplace may impair several aspects, such as individual health or job performance [ 37 ]. According to the COR theory, when an individual’s resources are lost and fail to produce the expected return after a large amount of resource investment, the anxiety and job performance generated by work stress increase.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Briefly, frontline miners, with lower OHW in the Min and Dig, were given responsibility for production targets, representing a higher level of intensive workload. Working conditions are undesirable, including worse physical environmental conditions and higher risks (Senapati et al., 2020). Again, they have to accomplish the operational tedious procedures and tasks and fulfill their work responsibilities on a tight schedule.…”
Section: Resultsmentioning
confidence: 99%
“…The three categories consist of maintenance, electricians' teams, etc. They are also plagued by noise, high temperature, high humidity, insufficient working space, posture discomfort, and manual tool vibration (Senapati et al., 2020).…”
Section: Resultsmentioning
confidence: 99%